A review of robotics and autonomous systems in the food industry: From the supply chains perspective. (December 2020) - Duong, Linh N.K.; Al-Fadhli, Mohammed; Jagtap, Sandeep; Bader, Farah; Martindale, Wayne; Swainson, Mark; Paoli, Andrea
Abstract: Background. An increasing global population means resource utilisation and food security remain the critical global challenges. Robotics and autonomous systems (RAS) have been applied to improve productivity, and their role in enhancing supply chain operations is explored here. Scope and approach. Researchers have studied ways to adopt and integrate RAS into the food industry. However, most of the current literature focuses on the technological impact of RAS. In contrast, this paper discusses the adoption of RAS in the food industry from the supply chain perspective with regard to the supply chain operations. Key findings and conclusions. The study has selected 54 papers using a nine-step systematic review process. This research analysed the use of RAS across five major themes of the food supply chain, including food quality, food safety, food waste, supply chain efficiency, and supply chain analysis. The role of RAS the data availability, cybersecurity, skill capability, and financial costs are discussed in the context of adopting RAS in food supply chains. Future research directions are proposed with the aim of enhancing the application of RAS in food supply chain operations. Highlights: The adoption of RAS in the food industry is reviewed from the supply chain perspective. 54 papers were collected from a nine-step systematic review process. The adoption of RAS was analysed based on five major themes of food supply chain. The role of RAS, the data availability, cybersecurity, skill capability, and financial costs are main issues in the adoption. Several future research directions were identified to boost the adoption of RAS in the food supply chain.